Absence of relaxor-like ferroelectric phase transition in (Pb,Sr)TiO3 thin films - Pontes, F. M.; Leal, S. H.; Leite, E. R.; Longo, Elson [UNESP]; Pizani, P. S.; Chiquito, A. J.; Machado, MAC; Varela, José Arana [UNESP] (Springer, 2005)
We have performed dielectric and micro-Raman spectroscopy measurements in the 298 - 673 K temperature range in polycrystalline Pb0.50Sr0.50TiO3 thin films prepared by a soft chemical method. The phase transition have been investigated by dielectric measurements at various frequencies during the heating cycle. It was found that the temperature corresponding to the peak value of the dielectric constant is frequency-independent, indicating a non-relaxor ferroelectric behavior. However, the dielectric constant versus temperature curves associated with the ferroelectric to paraelectric phase transition showed a broad maximum peak at around 433 K. The observed behavior is explained in terms of a diffuse phase transition. The obtained Raman spectra indicate the presence of a local symmetry disorder, due to a higher strontium concentration in the host lattice. The monitoring of some modes, conducted in the Pb0.50Sr0.50TiO3 thin films, showed that the ferroelectric tetragonal phase undergoes a transition to the paraelectric cubic phase at around 423 K. However, the Raman activity did not disappear, as would be expected from a transition to the cubic paraelectric phase. The strong Raman spectrum observed for this cubic phase is indicative that a diffuse-type phase transition is taking place. This behavior is attributed to distortions of the perovskite structure, allowing the persistence of low-symmetry phase features in cubic phase high above the transition temperature. This result is in contrast to the forbidden first-order Raman spectrum, which would be expected from a cubic paraelectric phase, such as the one observed at high temperature in pure PbTiO3 perovskite.